LARVICIDAL ACTIVITY of the ESSENTIAL OIL of the LEAVES OF Camará AGAINST Aedes aegypti - Nascimento, Jéssica da Silva; Aguiar, Júlio César Ribeiro de Oliveira Farias de; Navarro, Daniela Maria do Amaral Ferraz (Caderno Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The Aedes aegypti mosquito is present in several tropical and subtropical climate countries so that, according to the world health organization, about 2.5 billion people are subject to chikungunya, dengue, zika virus and yellow fever. These diseases can lead to death or impair the daily activities of those infected. This vector is present in all Brazilian states and the use of insecticides is one of the ways to combat it. But new strains resistant to the usual insecticides are becoming increasingly common, thus requiring a search for new larvicides. Thus essential oils have been showing promising results in various areas of scientific research. These include the search for insecticides with little or no toxicity, and plants emerge as an alternative to more effective and less toxic formulations. Thus, the objective of this work was to evaluate the use of essential oil of Camará leaves as a larvicidal agent against A.aegypti larvae. The leaves of the biological material were collected in the municipality of Camocim de são Félix / PE. 259g of leaves were shredded and the essential oil extracted by hydrodistillation. To evaluate larvicidal activity, 20 larvae in stage L4 were submitted to different concentrations (645µg / mL, 350µg / mL, 110µg / mL), and mortality was observed at 100, 85 and 35% after 48 hours. This biological activity is due to the presence of germacrene D major compounds, 25.50%; Germacrene D-4-ol, 18.84% and bicyclogermacrene, 11.33% in oil. Therefore, it can be considered that the essential oil analyzed in the tested concentrations was effective in controlling A. aegypti larvae.